Impaired recognition of disgust is related to subcortical volume loss in amyotrophic lateral sclerosis. (31st December 2021) - Canu, Elisa; Leocadi, Michela; Castelnovo, Veronica; Magno, Maria Antonietta; Riva, Nilo; Poletti, Barbara; Silani, Vincenzo; Filippi, Massimo; Agosta, Federica
Abstract: Background: The impairment in detecting disgust in Amyotrophic Lateral Sclerosis (ALS) has been hypothesized to be related with the integrity of subcortical structures. However, this has not been demonstrated yet and was the aim of the study. Method: Twenty ALS patients without cognitive/behavioural symptoms and 52 matched healthy controls (HC) underwent a brain MRI scan and a neuropsychological assessment including the Comprehensive Affect Testing System (CATS) investigating emotion recognition. Composite scores were calculated by summing up the correct answers for each emotion. Gray matter (GM) volumes of the subcortical structures were obtained using FIRST in FSL. Sociodemographic, cognitive and MRI data were compared between groups. In ALS patients, CATS significant findings were correlated with the subcortical volumes, ECAS performances, patients' mood and behaviour. Result: ALS patients performed significantly worse than HC at the CATS, and they were significantly less able to recognize disgust. No GM volume differences were observed between groups. In ALS patients, a low performance in disgust recognition was related with a reduced volume of the left pallidum and with low performances at the ECAS. Conclusion: In a sample of cognitively/behaviourally unimpaired ALS, we demonstrated an altered ability to correctly recognize disgust and a potential role of basal ganglia in the altered processing of this emotion. These findings, together with the relationship between the altered disgust recognition with lower ECAS performances in patients, suggest that disgust could be the first emotion to be hit in ALS cognitive decline. These findings offer new potential markers for monitoring extra‐motor progression in ALS. Supported by: Italian Ministry of Health (GR‐2013‐02357415); European Research Council (StG‐2016_714388_NeuroTRACK).